Assessment of Groundwater Vulnerability and Total Organic Carbon in the Shallow Groundwater of Wonosari City, Gunung Kidul, Yogyakarta, Indonesia - Soutsadachan Chandalsouk; Doni Prakasa Eka Putra; Wahyu Wilopo (Journal of Applied Geology, 2022)
Wonosari city is the capital of Gunung Kidul regency of Yogyakarta Special Province. The city is located in the karst plateau overlaying a succesion of limestone lithologies. The groundwater on this city is shallow and people used this groundwater as their daily water supply. This study aims to determine the intrinsic groundwater vulnerability and to identify the TOC level in groundwater also to investigate the relationship between groundwater vulnerability and TOC levels in the groundwater. Field observation was conducted on 40 groundwater occurrences (dug wells, bore wells and springs) to investigate the aquifer types, overlying lithology and depth to groundwater. At the same time, 16 groundwater samples were taken from the dug wells and analyse for the TOC content. Secondary data was also collected from previous researches especially the information of sub-surface lithology. Groundwater vulnerability was evaluate by using GOD method and correlation between groundwater vulnerability and TOC in groundwater was analyzed spatially and statistically by using map pverlaying, linear regression and Spearman’s rho test, respectively. The results showed that the groundwater vulnerability in the city is dominated by extreme and high vulnerability, covers about 84 % of study area. The TOC level in the groundwater ranges between  4.532 mg/L to 6.849 mg/L which showing a process of pollution loading may occur. Linear regression and Spearman’s rho value show that the TOC levels and  groundwater vulnerability has a moderate positive correlation with r2 value of about 0.324 for linear regression. Despite the moderate correlation, the research prove that the groundwater vulnerability map reveals on this study is good enough to represent the ability of natural condition in protecting the groundwater quality.